2022
DOI: 10.1001/jamanetworkopen.2022.0254
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Following Receipt of Adjuvant Chemotherapy With and Without Bevacizumab in Patients With Lymph Node–Positive and High-Risk Lymph Node–Negative Breast Cancer

Abstract: IMPORTANCE Breast cancer treatment can impact not only short-term health but may also affect longer-term quality of life (QOL).OBJECTIVE To describe and evaluate factors associated with diminished QOL following completion of active treatment. DESIGN, SETTING, AND PARTICIPANTSThis was a secondary analysis of a randomized clinical trial included patients with lymph node-positive or high-risk lymph node-negative breast cancer who had undergone definitive surgery and were enrolled in ECOG-ACRIN E5103, a multisite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This study used vision 4.0 of the FACT-B, which includes 4 domains: family/social, physical, functional, and emotional well-being, as well as a subscale for BC, which has better validity and reliability. The FACT-B was used by Rosenberg et al 32 to evaluate QOL in patients with BC receiving adjuvant chemotherapy 33 and Wan et al 33 demonstrated its good validity and reliability in Chinese patients with BC.…”
Section: Methodsmentioning
confidence: 99%
“…This study used vision 4.0 of the FACT-B, which includes 4 domains: family/social, physical, functional, and emotional well-being, as well as a subscale for BC, which has better validity and reliability. The FACT-B was used by Rosenberg et al 32 to evaluate QOL in patients with BC receiving adjuvant chemotherapy 33 and Wan et al 33 demonstrated its good validity and reliability in Chinese patients with BC.…”
Section: Methodsmentioning
confidence: 99%